Assessment of protease activity in hydrolysed extracts from SSF of hair waste by and indigenous consortium of microorganisms. (March 2016) - Yazid, Noraziah Abu; Barrena, Raquel; Sánchez, Antoni
Graphical abstract: Highlights: A SSF process is presented for obtaining proteases from hair wastes. Anaerobically digested sludge is a good co-substrate for the SSF. Proteases can be easily extracted from the reactor and lyophilized. The remaining material can be stabilized after protease extraction. Proteases obtained showed a good performance in the dehairing of cow hides. Abstract: Hair wastes from the tannery industry were assessed for its suitability as substrates for protease production by solid-state fermentation (SSF) using a pilot-batch mode operation and anaerobically digested sludge as co-substrate. Maximum protease activity (52, 230 ± 1601 U g −1 DM) was observed at the 14th day of SSF. Single step purification resulted in 2 fold purification with 74% of recovery by ultrafiltration with 10 kDa cut-off. The recovered enzyme was stable at a temperature of 30 °C and pH 11; optimal conditions that were determined by a central composite full factorial experimental design. The enzyme activity was inhibited by phenylmethylsulfonyl fluoride, which indicates that it belongs to serine protease group. The remaining solid material after protease extraction could be easily stabilized to obtain a final good quality compost-like material as the final dynamic respiration index was lower than 1 g O2 kg −1 OM h −1 . The lyophilized recovered enzymes were a good alternative in the process of cowhides dehairing with respect to the current chemical treatment, avoiding the production of solid wastes and highly polluted wastewaters. In conclusion, the entire process can be considered a low-cost sustainable technology for the dehairing process, closing the organic matter cycle in the form of value added product and a compost-like material from a waste.